Determinants of neonatal weight loss in term-infants: specific association with pre-pregnancy maternal body mass index and infant feeding mode. Issue 3 (17th January 2011) - Regnault, Nolwenn; Botton, Jérémie; Blanc, Laurence; Hankard, Régis; Forhan, Anne; Goua, Valérie; Thiebaugeorges, Olivier; Kaminski, Monique; Heude, Barbara; Charles, Marie-Aline; ,
Abstract : Objective: We aimed to study the determinants of neonatal weight loss measured on the third day of life in term-infants. Design: The EDEN mother–child cohort is a prospective study that recruited 2002 pregnant women before 24 weeks of gestation in two French university hospitals. Neonates were weighed every day until discharge that occurred on average 4.5 days after birth. Altogether, 1557 healthy term neonates with data on weight at day 3 and feeding mode available were included. The outcome variable was weight loss at day 3 (D3WL), expressed as a percentage of birth weight lost in the first 3 days of life. Our main explanatory variables were maternal pre-pregnancy body mass index (BMI), gestational weight gain, gestational diabetes, birth weight, gestational age and feeding mode. Results: Factors associated with greater D3WL, whatever the feeding mode, were: higher birth weight, gestational diabetes and caesarean section; higher gestational age was associated with a reduced D3WL. The association between maternal pre-pregnancy BMI and D3WL differed by feeding mode (interaction p value=0.0002). In breastfed babies, mean D3WL ranged from 4.9% for neonates of underweight mothers to 5.8% for neonates of obese mothers (p trend=0.0005). In formula-fed babies, D3WL was highest for neonates of underweight mothers (4.1%) and lowest for those of obese mothers (2.6%) (p trend=0.01). Conclusions: The lower D3WL in formula-fed neonates, especially in neonates of obese mothers, suggests a relative overfeeding in the early days compared with breastfed neonates, which may potentially have consequences on later health. Overweight and obese mothers may need extra support to prevent early breastfeeding discontinuation.